2011
DOI: 10.1007/s11266-010-9177-x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Commitment, Trust, Satisfaction, and Involvement on Donor Retention

Abstract: Due to certain developments in the business of fundraising, there exists an increasing necessity to theoretically and empirically analyze donor behavior. This article examines donor retention from the donor's point of view. It concretizes four antecedents and their relationships with one another. The influencing variables investigated are commitment, trust, satisfaction, and involvement. The empirical analysis conducted in Germany among donors of four representative social nonprofit organizations shows that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 54 publications
2
63
0
2
Order By: Relevance
“…Studies carried out within the European Union (EU) [13] and in the United States [14] show that these entities are important sources of employment and economic engines. In fact, the sector has been growing while consolidating itself as a complementary alternative to the public and private sector, giving goods and services to the entire social stratum [15,16].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies carried out within the European Union (EU) [13] and in the United States [14] show that these entities are important sources of employment and economic engines. In fact, the sector has been growing while consolidating itself as a complementary alternative to the public and private sector, giving goods and services to the entire social stratum [15,16].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This paper also expands zakat literature by suggesting the influencing factors on the trust. The factors were consistently reported in other non-profit organizations and charity-giving related studies (Sargeant & Lee, 2004;Sargeant & Woodliffe, 2007;Naskrent & Siebelt, 2011). The practical implication is information about the influencing factors can be utilized by zakat institutions to develop appropriate strategies to enhance the trust amongst the business owners.…”
Section: Conclusion and Implicationmentioning
confidence: 64%
“…The lack of understanding and respect for needs was found to run both ways. Naskrent and Siebelt [48] drew similar conclusions when they studied donor retention in Germany from the donor's point of view. They found that NGOs must communicate both qualitatively and emotionally about how the donor has contributed to the prior success and activities of the NGO if they want to foster repeat giving.…”
Section: Repeat Donor Intention As Expressed By the Donors Themselvesmentioning
confidence: 72%
“…Sargeant [46] and Bennett and Ali-Choudhary [47] define a committed giver as one who has made monetary contributions to the NGO in the preceding 18 months. Naskrent and Siebelt [48] define retention by identifying two types of donors: committed givers and cash donors. Committed donors are active donors with ongoing direct debits and cash donors are those who have given two or more cash gifts to the NGO, including one within the preceding 24 months.…”
Section: Donor Retention As One Expression Of Loyalty To An Ngomentioning
confidence: 99%
See 1 more Smart Citation